Banana Trees - (:unkn) unknown (Stephens and Scott Ltd. Trinidad, 2009)
Labourers in the fields inspect the banana "trees".
Colour: Black and White; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Bananas--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Agricultural laborers--Trinidad and Tobago